Sustentabilidade na piscicultura: Análise dos sistemas integrados e independentes de Nova Aurora-PR - Gerona, Leticia Natânia Pereira Blanco (2021)
Advances in fish farming have contributed, worldwide, not only to the expansion of production, but also as an alternative to supply the market. However, this growth has led to the need for fish farmers to seek measures that can reduce impacts on the environment to become more sustainable. In the production chain of fish farming in Brazil there are two predominant cultivation systems: the integrated cultivation system – which occurs when the various production processes are controlled by the same company, such as the supply of fingerlings, feed, technical assistance, in which a contract is signed between the company, called an integrator, and the producer designated as integrated, which provides the infrastructure and labor in production – and the independent system, in this the producer acquires the fingerlings and the feed of suppliers, developing the crop independently, being responsible for the entire production process of fish farming. This study aimed to analyze the contribution to the sustainability of integrated and independent fish farming systems in Nova Aurora-PR, considering the economic, environmental and social dimensions of sustainability. The research approach was qualitative and descriptive and, as a data collection instrument, we used the semi structured interview conducted with ten fish farmers from the independent system and ten integrated fish farmers. The analysis and interpretation of the data from the interviews considered whether or not they meet the sustainability indicators suggested in the literature. From this indicator, it was observed the proportion of producers who indicated sustainable practices in each item analyzed, thus resulting in a classification in four different levels of contribution to sustainability: unsustainable, unsustainable, partially sustainable and sustainable. With this classification of the items, it was possible to classify a proportional result for each dimension of sustainability for comparison between the groups of integrated and independent producers. The results showed that the integrated system provides a greater contribution to sustainability in the environmental dimension, especially in items related to effluent treatment, adequate management of water resources and water quality. In the social dimension, the integrated system presented a greater contribution to sustainability, due to the item related to training and training. On the other hand, the independent system has favored, to a greater extent, the economic dimension of fish farming, contributing to sustainability especially for items related to family economic growth. Although the differences between the groups can be considered small, it was possible to conclude that the integrated fish farming system made a better contribution to sustainability in the environmental and social dimensions, while the independent system contributed, to a greater extent, to sustainability in the economic dimension, even though both contribute to the sustainability of fish farming in Nova Aurora PR. This study contributes the awareness of fish farmers in Nova Aurora-PR about the need to reconcile economic growth with the social and environmental dimensions of sustainability. In addition, it contributes with a useful survey to support the formation of public policies in the municipality that promote the growth of activity, encouraging the training of fish farmers, in both production systems and, further, providing greater sustainability of the activity in rural properties.